2023
DOI: 10.1093/europace/euad023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dronedarone vs. placebo on atrial fibrillation progression: apost hocanalysis from ATHENA trial

Abstract: Aims This post hoc analysis of the ATHENA trial (NCT00174785) assessed the effect of dronedarone on the estimated burden of atrial fibrillation (AF)/atrial flutter (AFL) progression to presumed permanent AF/AFL, and regression to sinus rhythm (SR), compared with placebo. Methods and results The burden of AF/AFL was estimated by a modified Rosendaal method using available electrocardiograms (ECG). Cumulative incidence of perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A posthoc analysis of the ATHENA trial showed that dronedarone can be a useful antiarrhythmic drug for early rhythm control, as it reduces the burden of AF/atrial flutter (AFL) progression to permanent AF/AFL and increases the regression to sinus rhythm (SR) compared to placebo [129]. Another posthoc analysis of the ATHENA trial found that dronedarone has both rhythm-and rate-controlling properties, as it prolongs the time to AF/AFL recurrence, reduces the need for electrical cardioversion, and decreases the likelihood of permanent AF/AFL [130].…”
Section: Management Of Patients With Hfpef and Af Hfpef-af And Medica...mentioning
confidence: 99%
“…A posthoc analysis of the ATHENA trial showed that dronedarone can be a useful antiarrhythmic drug for early rhythm control, as it reduces the burden of AF/atrial flutter (AFL) progression to permanent AF/AFL and increases the regression to sinus rhythm (SR) compared to placebo [129]. Another posthoc analysis of the ATHENA trial found that dronedarone has both rhythm-and rate-controlling properties, as it prolongs the time to AF/AFL recurrence, reduces the need for electrical cardioversion, and decreases the likelihood of permanent AF/AFL [130].…”
Section: Management Of Patients With Hfpef and Af Hfpef-af And Medica...mentioning
confidence: 99%
“…The gold standard diagnosis of AF is 12-lead ECG recording. Since the examination is difficult to perform in mass field surveys, several tools have been validated for screening with convincing reliability [5][6][7][8][9][10][11][12][13][14]. We used Alivecor Kardia software embedded on a smartphone with the aim to explore the epidemiological profile of AF a poorly recognized disease among the general Congolese partly because such information is not yet available.…”
Section: Introductionmentioning
confidence: 99%